25-gauge vitrectomy with gas tamponade for uncomplicated rhegmatogenous retinal detachment: experienced vs. inexperienced surgeons - Martin Pencak; Zbynek Stranak; Jakub Dite; Jana Vranova; Pavel Studeny; Miroslav Veith (PeerJ)
Background Rhegmatogenous retinal detachment (RRD) is a vision-threatening condition that requires prompt surgical intervention. With advancements in surgical techniques and equipment, pars plana vitrectomy (PPV) has become increasingly popular for the management of RRD. This, in turn, requires beginner vitreoretinal surgeons to be able to manage RRD early in their training. Introduction Comparison of the results and complication rates of a 25-gauge (25 g) PPV with gas tamponade for RRD between experienced and inexperienced surgeons. Methods This is a retrospective comparative consecutive case series study of patients with uncomplicated RRD treated with 25 g PPV with gas tamponade. Patients were divided into two groups: in the experienced surgeon group (ESG), the procedure was performed by an experienced vitreoretinal surgeon, in the inexperienced surgeon group (ISG), it was performed by two inexperienced surgeons. Anatomical and functional results and complication rates were compared between the two groups. Results A total of 216 eyes were included in the study. In the ESG (106 eyes), the single operation success rate was 94.3%, and the final success rate was 100%. In the ISG (110 eyes), the single operation success rate was 93.6%, and the final success rate was 100%. The difference in single surgery success rate between groups was not statistically significant (P = 0.828). The mean postoperative BCVA improvement was 0.348 decimal in the ESG and 0.405 decimal in the ISG (P = 0.234). The difference in complication rates between groups was not significant. Conclusions A 25 g PPV with gas tamponade for the treatment of RRD yields excellent anatomical results and improvement in best-corrected visual acuity (BCVA). With good technique and the use of modern vitrectomy machines and instruments, some inexperienced surgeons can achieve a high single-surgery success rate, suggesting a short learning curve. The complication rate is comparable between experienced and inexperienced surgeons.